Implementation of Ergo-Tourism and Local Wisdom to Design Tourism Village Governance Based on Balinese Cultur in Darma Buana, Belitang II South Sumatera Province - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Pratama, Yohanes Dicka (Ann Publisher, 2024)
This study aims to determine the implementation of the exploration stage carried out by stakeholders and local communities regarding the importance of ergo-tourism-based ecotourism governance design while preserving a harmonious environment with the local wisdom of Balinese culture-based tourism villages in Darma Buana Village. The research method used is ergonomics participatory action research, with an ergo-tourism and local wisdom approach, data collection through interviews, observations, and focused group discussions based on total ergonomics and ergo– entrepreneurship training. Action research was provided to stakeholders: members of the Tourism Awareness Group, members of the Prosperous Youth Movement, and local communities. The results showed that there is potential for natural tourism destinations and local wisdom, relaxation, arts and culture, family and religion. Darma Buana Village Tourism has the potential to be developed, so it is necessary to pay attention to ergo-tourism-based ecotourism governance and local wisdom as a form of prevention of environmental and tourist risks and safety. The research recommendation is to implement the integration of ergo-tourism and local wisdom as an ecotourism governance plan. Darma Buana Village managers need to improve digital branding by utilizing attractive social media content and massive updates based on Balinese culture, the uniqueness of customs as a portrait of a small Bali on the island of Sumatra, the implementation of ergonomic principles with a practical, comfortable, safe, healthy, and efficient orientation in every ecotourism work activity and local wisdom so that it is increasingly known and visited.